A universal adhesive containing copper nanoparticles improves the stability of hybrid layer in a cariogenic oral environment: An in situ study. (February 2022) - Vidal, Omar; de Paris Matos, Thalita; Núñez, Alejandra; Méndez-Bauer, Luján; Sutil, Elisama; Ñaupari-Villasante, Romina; Souta, Melissa Caroline; Pitlovanciv, Murilo; Gutiérrez, Mario F.; Loguercio, Alessandro D.
Abstract: Purpose: To evaluate how incorporating copper nanoparticles (CuNp) into a universal adhesive affects the antimicrobial activity (AMA), bond strength (μTBS), nanoleakage (NL), elastic modulus (EM) and nanohardness (NH) of resin–dentin interfaces, at 24 h (24 h) and after in situ cariogenic challenge (CC). Methods: CuNp (0% [control] and 0.1 wt%) was added to an adhesive. After enamel removal, the adhesives were applied to dentine surfaces. Each restored tooth was sectioned longitudinally to obtain two hemi-teeth; one of them was evaluated after 24 h, and the other was included in one of the intra-oral palatal devices placed in the mouths of 10 volunteers for 14 days in CC. After that, each hemi-tooth was removed, and any oral biofilm that formed was collected. The AMA was evaluated against Streptococcus mutans . For the 24 h and CC groups, each hemi-tooth was sectioned in the "x" direction to obtain one slice for each EM/NH evaluation. The remains of each hemi-tooth were sectioned in the "x" and "y" directions to obtain resin-dentin beams for μTBS and NL evaluation (24 h and CC). ANOVA and Tukey's test were applied (α = 0.05). Results: The presence of CuNp significantly improved AMA as well as all of the evaluated properties (24 h; p < 0.05). Although the adhesive properties (μTBS/NL) for all groups decreased after CC (p < 0.05), the adhesive containing CuNp showed higher μTBS and lower NL as compared to the copper-free adhesive (p < 0.05). The incorporation of CuNp maintained NH/EM values after CC (p < 0.05). Conclusions: Adding 0.1% CuNp to an adhesive may provide antimicrobial activity and increase its bonding and mechanical properties, even under a cariogenic challenge. Significance: This is the first in situ study proving that incorporating CuNp into an adhesive is an achievable alternative to provide antimicrobial properties and improve the integrity of the hybrid layer under in situ cariogenic challenge. Highlights: In situ models allowed the aging of adhesive interfaces under real oral conditions. Copper nanoparticles reduce adhesive degradation after aged in an in situ model. Copper nanoparticles improve the mechanical properties of hybrid and adhesive layer. Adhesive with copper nanoparticles has antimicrobial effect after a cariogenic dare.